Dendritic morphology changes in neurons from the ventral hippocampus, amygdala and nucleus accumbens in rats with neonatal lesions into the prefrontal cortex. Issue 6 (June 2015) - Lazcano, Zayda; Solis, Oscar; Díaz, Alfonso; Brambila, Eduardo; Aguilar‐Alonso, Patricia; Guevara, Jorge; Flores, Gonzalo
ABSTRACT Neonatal prefrontal cortex (nPFC) lesions in rats could be a potential animal model to study the early neurodevelopmental abnormalities associated with the behavioral and morphological brain changes observed in schizophrenia. Morphological alterations in pyramidal neurons from the ventral hippocampus (VH) have been observed in post‐mortem schizophrenic brains, mainly because of decreased dendritic arbor and spine density. We assessed the effects of nPFC‐lesions on the dendritic morphology of neurons from the VH, basolateral‐amygdala (BLA) and the nucleus accumbens (NAcc) in rats. nPFC lesions were made on postnatal day 7 (PD7), after dendritic morphology was studied by the Golgi‐Cox stain procedure followed by Sholl analysis at PD35 (prepubertal) and PD60 (adult) ages. We also evaluated the effects of PFC‐lesions on locomotor activity caused by a novel environment. Adult animals with nPFC lesions showed a decreased spine density in pyramidal neurons from the VH and in medium spiny cells from the NAcc. An increased locomotion was observed in a novel environment for adult animals with a PFC‐lesion. Our results indicate that PFC‐lesions alter the neuronal dendrite morphology of the NAcc and the VH, suggesting a disconnection between these limbic structures. The locomotion paradigms suggest that dopaminergic transmission is altered in the PFC lesion model. This could help to understand the consequences of an earlier PFC dysfunction in schizophrenia. To evaluate possible dendritic changes in neonatal prefrontal cortex lesions in schizophrenia‐related regions including nucleus accumbens, ventral hippocampus and basolateral amygdala, we used the Golgi‐Cox stain samples at PD35 and PD70. Our results suggest that neonatal prefrontal cortex damage alters dendritic parameters in limbic regions, and this has potential implications for schizophrenia. Synapse 69:314–325, 2015. © 2015 Wiley Periodicals, Inc.